1990
DOI: 10.1093/jnci/82.11.952
|View full text |Cite
|
Sign up to set email alerts
|

New Variants of the B16 Melanoma: Tumorigenicity and Metastatic Properties Under Different Culture Conditions

Abstract: Variants of the B16 melanoma exhibiting markedly different tumorigenic and metastatic potential in Ay/a and a/a C57BL/6J syngeneic mice were investigated and compared, with respect to their relative growth and metastatic potential after culture under different conditions. Over 2 to 6 months of growth, in vitro cells demonstrated a rapid and significant decrease in their ability to form spontaneous lung colonies. Such a decrease depended on the conditions of culture. We suggest that the in vitro environment inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…After long-term culture (1 year) in EMEM of B16 control, MMBl6, and AMB16 cells, spontaneous pulmonary metastases disappeared in C5Fla, CJC, and Cclc mice (P < 0.005). Thus, we observed that long-term culture was accompanied by the loss of spontaneous metastatic ability, as reported previously (Aubert et al, 1990).…”
Section: Differentiation and Numbers Of Pulmonary Metastases In Albinsupporting
confidence: 88%
See 2 more Smart Citations
“…After long-term culture (1 year) in EMEM of B16 control, MMBl6, and AMB16 cells, spontaneous pulmonary metastases disappeared in C5Fla, CJC, and Cclc mice (P < 0.005). Thus, we observed that long-term culture was accompanied by the loss of spontaneous metastatic ability, as reported previously (Aubert et al, 1990).…”
Section: Differentiation and Numbers Of Pulmonary Metastases In Albinsupporting
confidence: 88%
“…Our results show that the production of melanin under Merent culture conditions, in the metastatic variant tumors and in pulmonary metagtases, exhibited a marked degree of heterogeneity that was unrelated to the metastatic phenotype. The evolution of the metastatic properties, in the course of sequential passages in cell culture, was manifested as a rapid decrease in the numbers of spontaneous and experimental metastases (Aubert et al, 1990). The B16 melanoma and its metastatic YB16 and MB16 variants, with the progression of tumors in vivo and the loss in vitro of metastatic ability, should prove to be an excellent model system for discrimination between the types of cellular change that occur throughout the stages of varying metastatic potential and differentiation that are related to genetically and epigenetically modulated conditions.…”
Section: Frequency Of Pigmented Metastases (Percentage) In Albino Recmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these conclusions relied upon immunohistologic analysis and antibody ferentiation, adhesive, and metastatic properties of melanoma cells. Studies of tumor growth in syngeneic perturbation experiments, the present study makes use of NG2/HMP-expressing and nonexpressing mouse C57Bl/6 mice show that in the case of both B16F1 and B16F10 cells, expression of NG2 enhances subcutane-proliferative capacity of cells both in vitro and in vivo (Aubert et al, 1990;Tsukamoto et al, 1991). In some ous tumor growth.…”
Section: Discussionmentioning
confidence: 77%
“…In consonance with this idea, it has been proposed that the concept of dedierentiation in oncology 27 is associated with an increase in the proliferative capacity of the cells both in vitro and in vivo. 1,51 Sometimes this is attributable to changes in the repertoire of cell surface antigens expressed by transformed cells at varying stages of dierentiation. 15 Recent ®ndings show that not only is NG2 expressed in human brain sections 45 , but in our laboratory we have found NG2 +ve cells within human glionia sections.…”
Section: Discussionmentioning
confidence: 99%